PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Zulkipli Zulkipli (JURNAL EKOMBIS, 2018)
The objective of this research is to see the relation of fiscal decentralisation with the growth of the indonesian economy from year 2010 to 2014. The study uses panel data gathered from the Indonesian Ministry of finance and Indonesian Statistical Bureau (BPS) covering General Allocation Fund (Dana Alokasi Umum/DAU), Specific Grant (Dana Alokasi Khusus/DAK) and Revenue-Sharing (Dana Bagi Hasil/DBH), and provincial Real Regional Gross Domestic Product (Produk Domestik Regional Bruto Riil/PDRB). Data is then analysed panel data analysis model. There are four variables taken into the equation. While PDRB is treated as dependent variable, DAU, DAK and DBH act as independent variables. Regional data are also grouped into three regional setting: (1) Sumatera, (2) Java, and Bali (3) Sulawesi, Kalimantan and Eastern Indonesia. The purpose of this categorisation is to see the statistical output differences resulted from these three examined regions. The research analysis shows that fiscal decentralisation has a positive influence on the economic growth. DAU and DBH have positively influenced the PDRB. On the other hand, DAK has a negative influence on PDRB. There are six regions that have positive heterogenity. They are Jakarta, East Java, West Java, Middle Java, Banten and North Sumatera. Its means that they have higher heterogenity among others. The regions that have lowest heterogenity are Riau Islands, Papua, West Papua, Maluku and East Nusa Tenggara. Finally, this research suggests that central government should guarantee the continuity of fiscal transfer to regions that have shown their fine performance in enhancing the local economic growth. At the same time, local governments should make a better use the use of fiscal transfers based on priority sectors in order to accelerate the growth of their local economy.Key Words: Economic growth and Fiscal decentralisation